GAMBARAN EFIKASI DIRI DENGAN KETERAMPILAN KOMUNIKASI PESERTA DIDIK KELAS XI DI SMA - Rozalia, Sindi; Nadiyah, Alzhafirah; Putri, Rani Mega (Jurnal Empati Bimbingan dan Konseling, 2024)
This study aims to analyze the relationship between self-efficacy and communication skills of class XI students at SMA Negeri 10 Palembang. This research uses quantitative methods with correlational design. The total population in this study was 605 students and a sample of 86 students using simple random sampling techniques. Data analysis was performed using the Pearson Product Moment formula in the SPSS version 16.0 application. The results of the analysis obtained by most students had self-efficacy dominant is in the low category, namely 31 students while in the variable communication skills dominant is the medium category, namely 32 students then obtained a correlation coefficient of sebesar = 0,559 which is where = 0,559 0,214 so that the research hypothesis Ha is accepted, namely there is a positive relationship between self- efficacy and communication skills of class XI students at SMA Negeri 10 Palembang, which means that the higher the self-efficacy, the higher the communication skills.